Kamu alacaklarının cebren tahsili - Sağlam, Hakkı (My University, 2004)
Tez Özeti Bu tez çalışmasında kamu alacaklarının cebren tahsili uygulaması ile gerek borçlular ve gerekse alacaklı kamu idarelerinin karşılaştığı sorunlar sonuçlarıyla birlikte incelenmeye çalışılmıştır. 6183 Sayılı Amme Alacaklarının Tahsil Usulü Hakkında Kanun'un Devlete, İl Özel İdarelerine ve Belediyelere ait vergi, resim, harç, para ve vergi cezası, muhakeme masrafı, gecikme zammı, faiz gibi kamu alacaklarının tahsil şeklini göstermektedir. Kamu alacaklarının takip ve tahsilindeki prensipleri iki genel esasta toplamak mümkündür. Bunlardan biri, kamu alacağını ödemekle mükellef olanlara, ödeme bakımından her türlü kolaylığı göstermek, diğeri de, kamu idarelerinin alacaklarını emniyet altında bulundurarak, kolay ve seri bir şekilde tahsil etmeleridir. Kamu idarelerine borçlu olanlar bu borçlarını belirtilen vadelerde ödemek mecburiyetindedirler. Oldukça geniş bir uygulama alanı bulunan 6183 sayılı kanun, bu tez çalışmamızda cebren tahsil yönüyle ele alınmıştır. Kanundan ve uygulamadan kaynaklanan sorunların ortaya konulması, analiz edilmesi ile sorunlara çözüm bulunması hedeflenmiştir. Kamu adına yapılan her türlü iş ve işlemlerde olduğu gibi, kamu alacaklarının tahsilinde de esas olan hukuk sistemi içinde işlemlerin tesis edilmesi ile bu işlemlerin yargı denetimine açık olması gereği vurgulanmıştır. Tüm bu veriler ışığında tez çalışması dört bölümden oluşmuştur. Birinci bölümde kamu alacaklarının hukuki niteliği ve kapsamı ile çeşitleri, kamu alacağı ile özel hukuktan kaynaklanan alacakların karşılaştırılması ve ayrıca, 6183 sayılı kanun kapsamında tahsil edilen her alacağın kamu alacağı olup olmadığı, 4389 sayılı Bankalar Kanunda yapılan değişiklik sonucu tasarruf mevduatı sigorta fonu uygulamaları da incelenmiştir. İkinci bölümde kamu alacaklarının güvence altına alınması ve iptal davası ile kamu alacakların güvence altına alma yollarının hukuksal niteliği ve kapsamı ile bu güvencenin haksız rekabete yol açıp açmadığı işlenmiştir. Üçüncü bölümde kamu alacaklarının cebri icra yoluyla tahsile hazırlık, ödeme emri düzenlenmesi ve hukuki niteliği, ödeme emrine karşı dava açma, teminatlı alacaklarda takip ile kamu alacaklıları arasında işbirliği yöntemleri incelenmiştir Dördüncü ve son bölümde ise; cebri tahsil yolları, menkul ve gayrimenkul mal haczi ile satışı, haciz dışında cebri icra yolları olan iflas ve konkordato olmak üzere istihkak davaları da ayrıntılı incelenecek ve bunlarla ilgili sonuçlar önerilmiştir. Sonuçta; kamu idarelerinin tahsil işlerine bakan personelinin genel olarak işini eksiksiz ve kusursuz bir şekilde yapabilmesi için ihtiyaç duyduğu bilgi birikimine sahip olmadığı, bu memurların görevlerini yerine getirirken Anayasal ve yasal sınırların genelde dışına çıktıkları, görülmüştür. Kamu alacaklarının cebri tahsil sonuçlarının bekleneni vermesi, ancak Anayasa ve hukuk devleti ilkesi dahilinde, alacakların ileri teknoloji kullanılarak zamanında takip ve tahsili ile mümkün olup; ayrıca zamanında ödenmeyen kamu alacakları için mali af çıkarılmaması konusunda Anayasa'ya hüküm konulması ile tamamlanmalıdır. Bu durum aynı zamanda yükümlülüklerini tam ve zamanında yerine getirenler açısından devlete güveni tazeleyeceği gibi, adalet ilkesini de etkin kılacaktır. Ayrıca İstanbul ili vergi gelirleri esas alınarak kanunun uygulaması ile ilgili yapılan analizler, tablolar halinde ek olarak sunulmuştur.

of Thesis In this work of a thesis the application of the collection of public receivables forcibly and the problems faced by both the debtors and the public administrations together with their results are attempted to be examined. The code About the Collection Procedures for the Public Receivables with number 6183 shows the collection procedures of the public receivables such as taxes, duties, charges, fines and tax fines, court expenditures, delay fines, and interests owed to the State, Special Administrations of the Provinces and to the Municipalities. It is possible for the principles for the follow-up and collection of the public receivables to be placed under two basic headings. One of them is to facilitate everything from the point of view of payment for the debtors who are obliged to pay the public receivables and the other is to hold the receivables of the public administrations under guarantee and to collect them in an easy and fast way. The debtors of the public administrations have the obligation of paying their debts on the indicated due dates. The code with number 6183 with a wide area of application is examined in this work of a thesis from the point of view of forcible collection. The objective is to find solutions to the problems by revealing and analyzing the problems sourcing from the code and its application. As all in the applications and procedures done in the name of the public, it is emphasized that the basis for the collection of the public receivables is the establishment of the procedures within the framework of the law system and the necessity for these procedures to be open to the auditing of trial. This study of thesis consists of four parts under the light of all this data. In the first part, the legal nature of the public receivables, and their extent and types; the comparison of public receivables and the receivables sourcing from special law; and further, whether all the receivables collected within the framework of the code with number 6183 is a public receivable or not; and the application of the Savings Deposits Insurance Fund as a result of the amendment made in the Banking Code with number 4389 are examined. In the second part, the subjects of the placement of the public receivables under guarantee; cancellation suits and the legal nature and extent of the means for the placement of the public receivables under guarantee together with whether this guarantee leads to unjust competition or not are examined. In the third part, the subjects of the preparation for the forcible collection of the public receivables through the enforcement office; the issue of the demand of payment and its legal nature; placement of suits against the demand of payment; follow-up for the receivables under guarantee; and the methods of cooperation between the public creditors are examined. In the fourth and last part, the forcible means of collection; the attachment and sales of movables and immovables; bankruptcy and composition with the creditors as the forcible means of enforcement besides attachment; and the actions for restitution are examined in detail and conclusions related with them are proposed. As a result, it is observed that the personnel employed for the collection of receivables of the public administrations do not have the background, which is required for them to have to carry out their duties fully and without any faults and that they generally go beyond the Constitutional and legal limits while they execute their duties. While it is only possible for the forcible collection of the public receivables to give the expected results by their timely follow-up and collection with the use of a higher technology within the framework of the Constitution and the principles of a state of law, it should be further completed with the inclusion of a provision in the Constitution for not announcing financial pardons for the public receivables not paid on time. While this situation would also renew the trust in the state from the point of view of the ones who meet their obligations fully and on time, it will also activate the principle of justice. Further, the analysis made in relation with the application of the code by taking the tax incomes of the city of İstanbul as basis are presented in tables as an attachment.
Keywords: Ekonomi; Kamu Maliyesi; Vergi dışı gelir